Chemical composition of a sample of bright solar‐metallicity stars1. Issue 10 (10th December 2015) - Caffau, E.; Mott, A.; Steffen, M.; Bonifacio, P.; Strassmeier, K. G.; Gallagher, A.; Faraggiana, R.; Sbordone, L.
Abstract: We present a detailed analysis of seven young stars observed with the spectrograph SOPHIE at the Observatoire de Haute‐Provence for which the chemical composition was incomplete or absent in the literature. For five stars, we derived the stellar parameters and chemical compositions using our automatic pipeline optimized for F, G, and K stars, while for the other two stars with high rotational velocity, we derived the stellar parameters by using other information (parallax), and performed a line‐by‐line analysis. Chromospheric emission‐line fluxes from Caii are obtained for all targets. The stellar parameters we derive are generally in good agreement with what is available in the literature. We provide a chemical analysis of two of the stars for the first time. The star HIP 80124 shows a strong Li feature at 670.8 nm implying a high lithium abundance. Its chemical pattern is not consistent with it being a solar sibling, as has been suggested. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)